Concentration in cross‐border research collaborations and MNCs ' knowledge creation in a host country - Zhang, Jingjing; Li, Jiatao; Yan, Yan; Xie, Zhenzhen (Strategic Management Journal, 2026)
Abstract Research Summary This study elucidates the previously underexplored structural heterogeneity inherent in multinational corporations' (MNCs) internal linkages by examining the concentration of cross‐border collaborations among inventors within host countries. Building on the boundary spanning literature, we develop a two‐stage framework identifying the knowledge distortion mechanism arising from this concentration: information overload in the cross‐country knowledge absorption stage and long transmission paths and knowledge hoarding in the within‐country diffusion stage. Both hinder local knowledge creation. We further propose that cross‐country and within‐country network structures serve as contingencies moderating this relationship. The negative effects of collaboration concentration are exacerbated by structural holes in cross‐country networks but attenuated by the reach and density of within‐country networks. Empirical results based on American pharmaceutical MNCs from 1980 to 2008 support our hypotheses. Managerial Summary Effectively structuring internal cross‐border R&D collaborations is crucial for MNCs seeking to enhance local innovation outcomes. Although many firms focus on increasing cross‐border linkages, this study highlights that overlooking how collaborations are distributed among inventors can obscure key drivers of innovation performance. This research shows that given the number of cross‐border linkages, their concentration in the hands of a few inventors within a host country hinders local knowledge creation. The negative effect is amplified when the host country spans many structural holes in the cross‐country network. A well‐structured within‐country network with high reach or high density can help mitigate the effect by facilitating knowledge diffusion. Our findings highlight the importance of considering the structural and geographic configuration of internal MNC networks in global R&D strategy.